Discourse and translation: Comparative descriptive analysis of William Goldman's "The Princess Bride" and its French translation. - Hug, Christine. (University of Ottawa (Canada), 2000)
Translators often focus only on linguistic equivalence to the detriment of textuality, in translation and in the evaluation of translations. Looking for certain elements of discourse allows an analysis of meaning at other levels than term- or sentence-level. In this thesis, discourse analysis is applied to an entire text, William Goldman's The Princess Bride (New York: 1987). This postmodern novel draws on several different genres, but parodies them, and turns readers' expectations on their heads. The goal of this thesis is to see what happens to the elements of discourse in the French translation of this novel. The analysis deals first with macrotextual aspects including the paratext and the metatext. Examining the narrative framework highlights the play of the characters' and narrators voices' in the text. Comparing the original to the translation brings to light the translator's voice, one that reveals a tendency to normalization.
Keywords: Literature, Comparative.